2012
DOI: 10.2967/jnumed.112.103465
|View full text |Cite
|
Sign up to set email alerts
|

Small-Animal PET of Steroid Hormone Receptors Predicts Tumor Response to Endocrine Therapy Using a Preclinical Model of Breast Cancer

Abstract: Estrogen receptor-α (ERα) and progesterone receptor (PR) are expressed in most human breast cancers and are important predictive factors for directing therapy. Because of de novo and acquired resistance to endocrine therapy, there remains a need to identify which ERα-positive (ERα+)/PR-positive (PR+) tumors are most likely to respond. The purpose of this study was to use estrogen- and progestin-based radiopharmaceuticals to image ERα and PR in mouse mammary tumors at baseline and after hormonal therapy and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 28 publications
2
64
0
Order By: Relevance
“…Efforts PET agents for the in vivo imaging of ERα and ERβ are motivated by the prognostic value of the expression level of this receptor in cancer patients [165]. It is known, for example, that levels of the two ER subtypes change during the progression of breast cancer, so the independent measurement of both ERs might be useful in predicting disease outcome and response to endocrine therapies [171172]. Unfortunately, despite efforts so far to obtain 18 F-labeled compound 54 and 76 Br-labeled compound 55 , little evidence of ERβ-mediated uptake was observed in model systems, underlining the need for improved in vivo models to develop ERβ-selective radiopharmaceuticals for use as PET imaging agents to measure ERβ levels in breast tumors.…”
Section: Update On Chemical Classes Comprising Erα and Erβ Modulatorsmentioning
confidence: 99%
“…Efforts PET agents for the in vivo imaging of ERα and ERβ are motivated by the prognostic value of the expression level of this receptor in cancer patients [165]. It is known, for example, that levels of the two ER subtypes change during the progression of breast cancer, so the independent measurement of both ERs might be useful in predicting disease outcome and response to endocrine therapies [171172]. Unfortunately, despite efforts so far to obtain 18 F-labeled compound 54 and 76 Br-labeled compound 55 , little evidence of ERβ-mediated uptake was observed in model systems, underlining the need for improved in vivo models to develop ERβ-selective radiopharmaceuticals for use as PET imaging agents to measure ERβ levels in breast tumors.…”
Section: Update On Chemical Classes Comprising Erα and Erβ Modulatorsmentioning
confidence: 99%
“…Radionuclide isotopes that decay with emission of energetic gamma rays or positron particles coupled to targeting agents enable the highly sensitive in vivo detection and imaging of targets and metabolic processes using single photon emission computed tomography (SPECT) or positron emission tomography, respectively. The profound clinical significance of E2 in normal and diseased states including cancer has stimulated the development of diagnostic and therapeutic imaging agents targeting the nuclear ER in pursuit of the ultimate goal of effective noninvasive imaging for improved detection and management of therapy (Katzenellenbogen, 1980(Katzenellenbogen, , 1995Kiesewetter et al, 1984;Skaddan et al, 2000;Yoo et al, 2005;Ramesh et al, 2006;Seo et al, 2007;Fowler et al, 2012). This approach typically involves labeling the native steroid hormone, receptor ligand, or drug with a short-lived isotope (e.g., 18 F for positron emission tomography or 99m Tc for SPECT).…”
Section: G Estrogen Receptor-selective Ligandsmentioning
confidence: 99%
“…18 F]FES in ER-positive breast tumors in mice (Fowler et al 2012 ). PET imaging studies in rodents showed a good correlation of [ 18 F]FES tumor uptake with ER density, as determined in vitro (Aliaga et al 2004 ).…”
Section: Petmentioning
confidence: 93%